Distance Learning in John Stuart Mill’s Utilitarianism Perspective - Raihan Chaerani Putri Budiman (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This research explores distance learning from the perspective of John Stuart Mill's utilitarianism, employing a qualitative philosophical approach for an in-depth and contextual analysis. Using the Research on Actual Problems model, the study focuses on philosophical reflections on contemporary phenomena, specifically the global trend of distance learning. Descriptive and critical data analysis methods are employed, continuously referencing concrete issues in detail. The study examines how distance learning can be viewed as the best method to achieve happiness and benefit the greatest number of people, according to Mill's utilitarian principles. The analysis centres on factors contributing to collective happiness in distance learning, while also addressing potential problems such as the digital divide and the psychological effects of reduced social interaction within the framework of utilitarian theory.